Integrating the Value of Amanah in Islamic Education Governance: Perspectives from the Qur'an and Hadith: INTEGRASI NILAI AMANAH DALAM TATA KELOLA PENDIDIKAN ISLAM PERSPEKTIFAL-QURAN DAN HADIS - Raudhaturrahima Rahima; Mulyawan Safwandy Nugraha Mulyawan (JURNAL KAJIAN ISLAM MODERN, 2026)
The lack of application of Islamic values, especially amanah (trust), in Islamic education governance has led to weak accountability, integrity, and suboptimal quality of education in the midst of modern challenges such as technology and social change. This research aims to examine the concept of mandate from the Qur'an and Hadith and their integration to improve the governance of Islamic education. This research uses a qualitative descriptive method based on library research, data is analyzed from tafsir (Ibn Katsir, Fathul Bari), authentic hadiths, and current studies through identification, classification, and thematic synthesis. The results of the study show that the integration of trust significantly improves transparency, accountability, and holistic student development (cognitive, affective, spiritual), preventing corruption and nepotism while being in line with the principles of good governance. It provides practical recommendations for policymakers and educators to reform Indonesia's Islamic education through competency-based leadership and ethical management, creating high-quality responsive institutions